Multigenic forms of thrombophilia in habitual miscarige. - K. V. Voronin; N. V. Davidenko; T. O. Loskutova (Medičnì Perspektivi)
Miscarriage is an actual problem of modern obstetrics. The frequency of miscarriage is 10-25% of all pregnancies, and habitual abortion occurs in 5%. Habitual miscarriage is considered as a typical multifactorial disease, being the result of expression of functionally weakened versions of many genes on the background of adverse external and internal factors. The genetic nature of habitual miscarriage includes groups of genes responsible for hemostatic disorders and endothelial dysfunction. The aim of the study was to determine the frequency and the role of combination of allelic variants of thrombophilia genes and endothelial dysfunction in the development of habitual miscarriage. 109 women with recurrent miscarriage and 34 apparently healthy pregnant women were tested with allele specific polymerase chain reaction and genetic polymorphisms of coagulation factors and fibrinolysis (1691 G → A factor V Leiden, 20210 G → A prothrombin, 5G/4G PAI-1, -455 G → A fibrinogen β) and endothelial dysfunction (192 Q → R PON-1, 677 C → T MTHFR) were identified. The study showed the expediency of examination of women with habitual miscarriage for the presence of an inherited defect in the hemostatic system (gene mutations factor V Leiden, prothrombin 20210G → A, polymorphism of PAI-1 5G / 4G, fibrinogen β -455 G → A) and endothelial dysfunction (MTHFR gene polymorphism 677 C → T). A high frequency of multigene form of thrombophilia (two or more defects) in patients with habitual miscarriage - 80.7% was detected. Pathologic polymorphisms that cause fibrinolysis defects in combination with dysfibrinogenemia were identified the most frequently.